A simple, safe and easily accessible polyvinyl alcohol hydrogel for wound cleaning. (May 2022) - Li, Renpeng; Panxianzhi, Ni; Ye, Sheng; Yuan, Tun; Fan, Yujiang; Zhang, XingDong
Acute wounds are often contaminated by some kind of filth, and fluids are usually used to wash away the dirt, but the force of the fluid may cause secondary injury at the wound site or even increase the risk of infection. Hydrogels have several advantages over liquid scouring since they are less intense, more portable, and easier to control. In this study, poly(vinyl alcohol) was used to prepared a series of hydrogels, which were tested in terms of their properties and abilities to clean simulated dirty wounds. Simulated dirt and bacterial ( Serratia marcescens ) adhesion experiments demonstrated that they could effectively adhere to a certain amount of dirt or bacteria to achieve the purpose of wound cleaning. In addition to the bacterial adhesion, the antibacterial experiments also proved that the hydrogels have a certain inhibitory effect on the proliferation of E.coli and S.aureus . The hydrogels could change shape freely and exhibited excellent biocompatibility, ductility, and self-healing capabilities, which increase their service life and make them more suitable for treating wounds or acting as protection buffers. Based on all these characteristics, the developed hydrogel may be a potentially valuable material for wound cleaning.